The network always wins : how to influence customers, stay relevant, and transform your organization to move faster than the market - Hinssen, Peter, 1969- (McGraw-Hill, 2015)
"The Definitive Business Guide to Surviving and Innovating in the Digital Age.. The world is changing faster than ever. With the rise of new digital markets and the consequent network-ization of our environment, the phrase "The customer is always right" takes on a whole new meaning.. This powerful guide from serial entrepreneur and radical innovation consultant Peter Hinssen shows you how to keep your company up to speed with your market, engage with customers at a time when loyalty keeps fading into the background, and transform your organization into a network in order to thrive in this era of digital disruption ... The Network Always Wins provides step-by-step strategies to help you:. Reinvent your company--even after the market has flipped. Tap into the force of the network--and survive in a market characterized by speed, uncertainty, and complexity. Maintain relevance--and stay on top of emerging trends. Connect with your customers--and encourage them to interact. This business guide is as illuminating as it is pleasant and fun to read. It provides everything you need to adapt your organization for this exciting new age of networks and digital disruption. You'll learn how to evolve faster, connect deeper, and make better decisions than ever before. You'll find proven methods to speed up your reaction time, beat the clock of your competitors, and anticipate consumer trends before they even happen.. In today's fast-moving marketplace, networks are power. This book shows you how to harness that power. For your company. For your customers. For your continued success in the digital age.."--